The effectiveness of singing therapy in counseling services to improve language skills of children with special needs - Munawwarah; Siregar, Alfin (Universitas Islam Negeri Raden Intan Lampung, 2025)
Language development remains a central challenge for children with special needs, requiring counseling interventions that are both engaging and developmentally appropriate. This study examined the effectiveness of singing therapy integrated into counseling services at SLB-C Santa Lusia Medan, Indonesia, using a quantitative experimental design with a pretest–posttest control group approach. Thirty students with special needs were randomly assigned to an experimental group (n = 15) and a control group (n = 15). The experimental group received 12 sessions of singing therapy over six weeks, while the control group participated in conventional learning activities. Language skills were assessed using a validated language proficiency test covering vocabulary, pronunciation, and sentence comprehension. Data were analyzed using paired-sample and independent-sample t-tests, complemented by effect size calculations (Cohen’s d). The results demonstrated significant improvements in all language skill indicators in the experimental group compared to the control group (p < 0.001), with very large effect sizes (d = 1.39–1.48). These findings indicate that singing therapy is a highly effective counseling intervention for enhancing language skills among children with special needs and can be systematically implemented within counseling services in special education settings. counseling intervention for enhancing language skills among children with special needs in special education settings